Issues and challenges of senior citizens, analytical study from Sunnahic Perspective - Fatah Yasin, Raudlotul Firdaus; Fadhli, Ahmad Syarief (2019)
Globally, the population of the elderly aged 60 and above is rapidly increasing (Ageing, n.d.).